2021
DOI: 10.3389/pore.2021.1609756
|View full text |Cite
|
Sign up to set email alerts
|

FOXF1 as an Immunohistochemical Marker of Hilar Cholangiocarcinoma or Metastatic Pancreatic Ductal Adenocarcinoma. Single Institution Experience

Abstract: Cholangiocarcinoma (CCA) is a liver malignancy associated with a poor prognosis. Its main subtypes are peripheral/intrahepatic and hilar/extrahepatic CCA. Several molecular, morphological and clinical similarities between hilar/extrahepatic CCA and pancreatic ductal adenocarcinoma (PDAC) have been described. FOXF1 is a transcription factor which has been described to have prognostic significance in various tumors and it is involved in the development of bile ducts. The aim of this study is to determine occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The same applies to a study performed by Hrudka et al, in which immunohistochemical staining for the transcription factor FOXF1 proved to be quite specific (87%), but only in the distinction of peripheral intrahepatic cholangiocarcinoma versus hilar/extrahepatic cholangiocarcinoma and metastatic PDAC [ 31 ]. An investigation to distinguish the latter two entities was not conducted.…”
Section: Discussionmentioning
confidence: 66%
“…The same applies to a study performed by Hrudka et al, in which immunohistochemical staining for the transcription factor FOXF1 proved to be quite specific (87%), but only in the distinction of peripheral intrahepatic cholangiocarcinoma versus hilar/extrahepatic cholangiocarcinoma and metastatic PDAC [ 31 ]. An investigation to distinguish the latter two entities was not conducted.…”
Section: Discussionmentioning
confidence: 66%
“…In the present study, it was found that FOXF1-positive staining was mainly localized in the nucleus using IHC and IF staining. The nuclear expression of FOXF1 has also been found in hilar cholangiocarcinoma or metastatic pancreatic ductal adenocarcinoma ( 24 ). However, inconsistent results were observed in other types of cancer.…”
Section: Discussionmentioning
confidence: 99%